The place of inferior vena cava diameter and proBNP levels in determining the fluid balance of medical intensive care patients - ARIKAN, HÜSEYİN; KARAKURT, SAİT (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Fast and accurate detection of fluid balance in intensive care patients is of special significance. Many different methods are used to determine the fluid balance. In this study, we aimed to determine the fluid balance of patients in the medical intensive care unit using measurement of the inferior vena cava diameter and pro-brain natriuretic peptide (proBNP). Patients and Methods: Patients admitted to the medical intensive care unit between September 2013 and February 2011 were enrolled in the study. Inferior vena cava diameter was measured with a portable ultrasonography, according to guidelines published by the American Echocardiography Association. For pro BNP measurement, samples were taken simultaneously with ultrasonography. Results: One hundred and twenty-six patients (70 male,55.6%) were enrolled for the study. Mean age was 57.8 +/- 19.8 (18-89 years). Ninety-six (76.2%) patients were receiving mechanical ventilation support. Mean proBNP levels were 10645.88 +/- 12731.08 pg/ml. There was no statistically significant difference between proBNP levels in patients according to the fluid status. Collapsibility index was not statistically different according to the volume status (p=0.75). Conclusion: proBNP levels were not correlated with the fluid balance. proBNP levels and inferior vena cava diameters were negatively but weakly correlated.
Keywords: Fluid balance; Inferior vena cava diameter; proBNP; Ultrasonography; BRAIN NATRIURETIC PEPTIDE; ULTRASONOGRAPHIC MEASUREMENT; RESPIRATORY VARIATION; VOLUME; HEART; RESPONSIVENESS; BIOIMPEDANCE; ULTRASOUND; PRESSURE